The Recap of Indonesia G20 Presidency in Bali - I Made Yogi Pramana (Bali Tourism Journal, 2022)
An international forum is a group discussion panel that helps world leaders exchange ideas and thoughts, which will later impact a country's economic and political policies or several countries. In November 2022, there were at least two important international meetings. First, the COP27 meeting in Cairo, Egypt, on 10 November 2022, and G20 Bali Summit. Indonesia had gone through a long steep road until it could finally reach a mutual agreement at the G20 Presidency in Bali, prioritizing health, digital transformation, and energy transition. However, the meeting of the head of the G20 member state was overshadowed by a global crisis. In the closing ceremony of the Indonesia G20 Presidency, Indonesian President Joko Widodo expressed his delight that the G20 Bali Leaders' Declaration had been well adopted and approved. G20 Bali Leaders' Declaration resulted from the series of G20 Indonesian presidency activities. It strived to provide various best solutions for one year of leadership amid various crises and new challenges. The effect of the high-level conference or the G20 Presidency in Bali in November 2022 was surging demand for investors all around the globe. Economic uncertainty in 2023 led to the government's decision to raise funds from investors. Since the end of 2022, Jokowi repeatedly brought up the importance of investors in Indonesia to face the threat of recession in 2023. Jokowi expected that the investment climate in Indonesia would be made easier.